Self-compacting ardealite road base material and preparation method thereof

A self-compacting phosphogypsum road base material with controlled ratios of phosphogypsum, cement, and aggregates addresses the utilization challenge, enhancing strength and durability, and reducing environmental impact.

CN119191800AActive Publication Date: 2024-12-27HUBEI YITONG CONSTR ENG CO LTD

Patent Information

Application Number
CN202411092447.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-09
Publication Date
2024-12-27
Estimated Expiration
2044-08-09

AI Technical Summary

Technical Problem

Phosphogypsum, a byproduct of phosphoric acid production, is difficult to utilize due to its impurities and has low utilization rates in traditional road base materials, leading to environmental pollution and inefficient waste management, while existing road base materials using phosphogypsum suffer from instability and cracking issues.

Method used

A self-compacting phosphogypsum road base material composed of phosphogypsum, cementitious materials, aggregates, and admixtures, with controlled ratios to enhance hydration and mechanical strength, incorporating a slow-release agent and anti-cracking agents to improve fluidity and durability.

Benefits of technology

The material achieves high mechanical strength, fluidity, and durability, effectively consuming phosphogypsum, reducing environmental impact, and preventing cracking, with a filling slump expansion index of SF1 level and compressive strength of ≥8MPa, offering economic and social benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191800A_ABST
    Figure CN119191800A_ABST
Patent Text Reader

Abstract

The invention provides a self-compacting ardealite road base material and a preparation method thereof, and belongs to the technical field of building materials, the base material comprises the following components in percentage by mass: 40-55% of ardealite, 4-13% of a cementing material, 35-50% of aggregate, 0.2-0.7% of an additive and the balance of water, wherein the cementing material comprises cement and slag powder, and the water-cement ratio is 4.5-7.5. According to the self-compacting phosphogypsum road base material, the properties of phosphogypsum and a cementing material are fully exerted, the filling slump expansion index of the formed self-compacting phosphogypsum road base material reaches SF1 level (550-655 mm), the expansion time T500 index reaches VS1 level (larger than or equal to 2 s), the 28-day compressive strength is larger than or equal to 8 MPa, the water softening coefficient is larger than or equal to 85%, and the water absorption rate is smaller than or equal to 10%. According to the phosphogypsum road base material disclosed by the invention, cement with a relatively low mixing amount is used, so that early-stage diseases of a road base are effectively overcome or avoided; and meanwhile, the ardealite with medium and high doping amount is used, so that the ardealite can be quickly consumed, the inventory is reduced, the stacking problem is relieved, and remarkable environmental, economic and social benefits are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a self-compacting phosphogypsum road base material and a preparation method thereof. Background Art

[0002] Phosphogypsum is a solid waste produced when phosphate rock powder is used in the wet production of phosphoric acid and ammonium phosphate fertilizers in industry. About 4.5 to 5 tons of phosphogypsum are produced for every ton of phosphoric acid produced. Since phosphogypsum contains various impurities such as free carbon, hydrochloric acid, and sulfuric acid, it is difficult to fully utilize. At present, the main treatment method for phosphogypsum is accumulation, which seriously damages the ecological environment, not only pollutes groundwater resources, but also causes waste of land resources. Phosphogypsum has a certain hydration hardening strength. If it is used in road construction, it can not only consume a large amount of phosphogypsum, but also greatly reduce the construction cost of the road, which has significant social and economic benefits.

[0003] Traditional road base materials include cement stabilized soil, lime stabilized soil and fly ash crushed stone. In cement stabilized soil, cement, as a hydraulic material, produces colloids when it comes into contact with water. These colloids cannot form a unified whole in the soil, and will also destroy the structure and connection of the soil itself, creating a large number of unstable spaces. These spaces will become very fragile under the intrusion of water and temperature changes. Therefore, the road base formed by cement stabilized soil is very easy to crack and has poor crack resistance.

[0004] Chinese patent document CN114716223A "A gangue-based road base material and preparation method thereof" discloses a road base material composed of a mixture of gangue A, gangue B, dihydrate phosphogypsum, carbide slag and a water reducer, but the amount of phosphogypsum added is small, the utilization rate of phosphogypsum is still low, which is not conducive to the rapid consumption of phosphogypsum, and the maximum compressive strength after 28 days is 4.2Mpa; Chinese patent CN117361979A "A crack-resistant and water-resistant phosphogypsum road base material and preparation method thereof" discloses a road base material composed of a mixture of calcined phosphogypsum, natural coarse aggregate (i.e. limestone), natural fine aggregate, silicate cement and additives, but the phosphogypsum needs to be calcined before use, and the amount of calcined phosphogypsum added is small, and the amount of natural coarse aggregate (limestone) used is large, which creates very favorable conditions for the formation of silica gypsum, which easily causes cracking and swelling of the road base, and the compressive strength after 7 days and 28 days is quite different.

[0005] Therefore, the present invention relies on actual engineering, starts from the selection and construction of base materials, and provides a self-compacting phosphogypsum road base material, which uses more phosphogypsum solid waste and less cement, plays a role in quickly consuming solid waste and reducing the occurrence of early road diseases; and delays the setting time of the base, facilitates construction and enhances mechanical strength. Summary of the invention

[0006] In order to solve the deficiencies of the prior art, the first purpose of the present invention is to provide a self-compacting phosphogypsum road base material. The phosphogypsum road base material of the present invention uses a relatively low amount of cement to effectively overcome or avoid the occurrence of early diseases of the road base; at the same time, the use of medium and high amounts of phosphogypsum can quickly consume phosphogypsum, reduce inventory, and alleviate stacking problems, which has significant environmental, economic and social benefits; the self-compacting phosphogypsum road base material of the present invention has good fluidity and high mechanical strength, and its filling slump expansion index reaches SF1 level (550-655mm), and the expansion time T 500 The indicators reach VS1 level (≥2s), 28-day compressive strength ≥8MPa, water softening coefficient ≥85%, and water absorption rate ≤10%.

[0007] The second object of the present invention is to provide a method for preparing a self-compacting phosphogypsum road base material, which is simple and easy to implement.

[0008] To achieve the first purpose, the technical solution adopted by the present invention is: A self-compacting phosphogypsum road base material comprises phosphogypsum, a cementitious material, an aggregate, an admixture, and each component is calculated in the following mass percentages: 40-55% of phosphogypsum, 4-13% of the cementitious material, 35-50% of the aggregate, and 0.2-0.7% of the admixture.

[0009] Preferably, the moisture content of the phosphogypsum is lower than 12%, and the particle size is 5-50 μm. The smaller the particle size, the more favorable it is for improving the uniformity and efficiency of the hydration reaction, and the more favorable it is for the hydration of ettringite.

[0010] Preferably, the cementitious material is S95 grade granulated blast furnace slag powder and 42.5 grade ordinary Portland cement; The mass ratio of the 42.5 grade ordinary Portland cement is 1-4%, and its fineness is expressed by the residue on the 45μm square hole sieve, which is not less than 5%; the initial setting time is not less than 45min, and the final setting time is not more than 600min; the stability is qualified by the boiling method, and the chemical requirements (mass fraction) are that the loss on ignition is not more than 5%, SO3 is not more than 3.5%, MgO is not more than 5%, and chloride ion is not more than 0.06%; the main chemical components are CaO (64~67%), SiO2 (20~23%), Al2O3 (4~8%), Fe2O3 (3~6%); The mass ratio of the S95 grade slag powder is 3-9%, and its density is not less than 2.8g / cm 3 , specific surface area not less than 400m 2 / kg, 28-day activity index not less than 95%, fluidity ratio not less than 95%, initial setting time ratio not more than 200%, water content not more than 1%, SO3 (mass fraction) not more than 4%, loss on ignition not more than 1%, insoluble matter (mass fraction) not more than 3%; the main chemical components are CaO (34-36%), SiO2 (34-36%), Al2O3 (16-18%), and Fe2O3 (1~2%).

[0011] After cement is dissolved in water, it becomes alkaline due to the hydrolysis of CaO. When granulated blast furnace slag is mixed with water alone, the reaction is extremely slow and the short-term strength is extremely low. However, it can be hydrated quickly in calcium hydroxide solution, and reacts faster in saturated calcium hydroxide solution and produces a certain strength. This is because it forms an alkaline solution with water, which can destroy the surface structure of the slag glass, making it easy for water to penetrate and undergo hydration reaction, causing the slag particles to disperse and disintegrate, and produce gelling calcium silicate hydrate and calcium aluminate hydrate. The main component of industrial waste slag phosphogypsum is CaSO4·2H2O, which hydrolyzes to generate excess free Ca 2 + With SO4 2- In an alkaline solution containing calcium hydroxide, adding a certain amount of calcium sulfate can fully exert the hydration activity of slag, produce much higher strength than adding alkaline substances alone, and generate hydrated calcium sulfoaluminate, which further improves the strength. The self-compacting phosphogypsum base material of the present invention fully utilizes the hydration activity of S95 grade slag powder, the alkali-activated characteristics of 42.5 grade ordinary Portland cement, and the property of some phosphogypsum participating in the reaction, and fully stirs and combines the three to generate a hydrated gelling substance with higher strength, thereby enhancing the strength of the base material.

[0012] The present invention strictly controls the dosage of phosphogypsum, cement and mineral powder (mass ratio is 40-50:1-4:3-9), thereby ensuring the water stability and compressive strength of the obtained road base material, effectively coordinating the early strength and late strength of the road base, reducing the influence of impurities in the phosphogypsum on product performance, and improving the water stability of the road base to prevent cracking.

[0013] Preferably, the mass ratio of the phosphogypsum to the cementitious material is 4-6:1, which controls the amount of ettringite formed, alleviates the self-shrinkage of the base material, and prevents cracking of the road.

[0014] Preferably, the aggregate is a mixture of sand and crushed stone, the sand is machine-made fine sand with a particle size of less than 4.75 mm, and the crushed stone is continuously graded crushed stone, which is fine crushed stone with a particle size of 5-10 mm and coarse crushed stone with a particle size of 10-20 mm, with a mass ratio of 3:7; The sand-gravel ratio is 0.2-0.3.

[0015] The mass ratio of the crushed stone is 30-41%, and the mass ratio of the machine-made fine sand is 8-10%.

[0016] Since phosphogypsum accounts for a relatively large proportion of fine aggregate, in order to make the self-compacting phosphogypsum base material have good fluidity, small-size aggregate is used and the content of needle-shaped flake aggregate is strictly controlled; the aggregate is designed according to the grading theory, and different aggregate particle sizes are matched and filled in the base material to form a tightly arranged multi-level spatial skeleton structure system with maximum friction, thereby improving the mechanical properties of the material.

[0017] Preferably, the admixtures include a slow-release agent and a water reducer, accounting for 0.3-0.4% of the total mass of the mixture.

[0018] The water reducer is a polycarboxylic acid water reducer, and the retarder is citric acid; the mass ratio is 1:0.1-0.3; the slow-release agent can stimulate the activity of slag powder and promote the generation of hydration products on the one hand, and control the hydration speed and prolong the setting time of cement on the other hand. An appropriate amount of citric acid can make the pores of the material smaller and more evenly distributed, which is beneficial to improving the density and durability of the base material.

[0019] Preferably, the admixture also includes an anti-cracking agent, which is polypropylene fiber; accounting for 0.01-0.03% of the mass of the admixture; the polypropylene fiber can effectively control the shrinkage of the material and microcracks caused by temperature changes, prevent the occurrence and development of cracks, and greatly improve the material's crack resistance, impermeability and impact resistance. Since polypropylene fiber has good ductility, after adding polypropylene fiber, the bridging effect of polypropylene fiber inhibits the expansion and formation speed of cracks, thereby improving the performance of the material and achieving the effect of preventing cracking.

[0020] The present invention prolongs the retarding time of the base material by adding a composite admixture, promotes the full hydration of slag powder, cement and phosphogypsum, enhances the strength of the base material and improves the durability of the material.

[0021] Preferably, the water reducer is an ester polycarboxylic acid water reducer.

[0022] The second object of the present invention is to provide a method for preparing a self-compacting phosphogypsum road base material, comprising the following steps: S1. Weigh each raw material according to mass percentage and set aside; S2. Take 80-90% of the total amount of phosphogypsum and 60-70% of the total amount of water and mix in a mixer, mix well to form a first mixture; S3. The cementitious material, the remaining phosphogypsum, aggregate, admixture and the remaining water are mixed in a mixer and mixed to form a second mixture; S4. Add the first mixture to the second mixture and mix and stir to form a third mixture; S5. Fill the formed third mixture into a molding mold, and after standing and molding, a self-compacting phosphogypsum road base material is formed.

[0023] Preferably, in S2, the stirring speed of phosphogypsum and water is 100-200 r / min, and the time is 1-3 min.

[0024] Preferably, in S3, the stirring speed of each component is 100-200 r / min, and the time is 2-4 min.

[0025] Preferably, in S4, the stirring speed of each component is 100-200 r / min, and the time is 3-6 min.

[0026] The phosphogypsum road base material prepared by the above method has good strength, durability and fluidity; its filling slump expansion index reaches SF1 level (550-655mm), and its expansion time T500 index reaches VS1 level (≥2s).

[0027] The present invention also provides a self-compacting phosphogypsum base road, which is paved with the self-compacting phosphogypsum base material.

[0028] Compared with the prior art, the present invention has the following beneficial effects: 1. The self-compacting phosphogypsum road base material of the present invention has a filling slump expansion index reaching SF1 level (550-655mm) and an expansion time T 500 The indicators reach VS1 level (≥2s), 28-day compressive strength ≥8MPa, water softening coefficient ≥85%, and water absorption rate ≤10%.

[0029] 2. The present invention provides a method for preparing a self-compacting phosphogypsum road base material. The preparation method is simple and easy to implement. The mixing ratio of each component of the road base material that meets environmental protection requirements and road performance is quickly and accurately obtained through a large number of indoor tests. The present invention uses cement with a relatively low dosage to effectively overcome or avoid the occurrence of early diseases of the road base. At the same time, the use of medium and high dosages of phosphogypsum can not only quickly consume phosphogypsum, reduce inventory, and alleviate stacking problems, but also has significant environmental, economic and social benefits.

[0030] 3. The phosphogypsum road base material of the present invention adjusts the mix ratio of each component, gives full play to the hydration characteristics of slag powder, the alkaline characteristics of cement and a small amount of phosphogypsum participating in the hydration reaction, and fully stirs and combines the three to generate a higher strength hydrated gelling material, thereby enhancing the mechanical properties of the phosphogypsum road base material.

[0031] 4. The present invention adopts a composite admixture containing a slow-release agent, a water reducing agent and an anti-cracking agent to effectively improve the compressive strength, setting time and shrinkage crack working performance of phosphogypsum road base materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] The present invention will be further described below in conjunction with the accompanying drawings and embodiments: Figure 1 This is the XRD diagram of the self-compacting phosphogypsum base material sample of the test example of the present invention. DETAILED DESCRIPTION

[0033] In the self-compacting phosphogypsum road base material provided by the present invention, cement mainly provides a sufficient alkaline environment for the system to stimulate the activity of slag powder, but too high a cement content will lead to the formation of too much calcium hydroxide, destroy the cementitious material, and affect the structural strength of the product, while the amount of slag powder added affects the amount of hydration products generated. As the slag powder content increases, more and more hydration cementation products are produced, which is beneficial to improve the bonding strength of the product. However, when the ratio of slag powder to cement is too high, the activity of the active component cannot be fully stimulated, and the continuous increase in strength in the later stage is likely to cause local cracks. Therefore, under the condition of a certain amount of cement, the present invention strictly controls the amount of slag powder so that the activity stimulation of the slag powder and the degree of hydration reaction are optimally matched. In addition, with the increase of slag powder content, the shape of ettringite changes from coarse rods to thin rods; when the slag powder content reaches 3-9% of the mixture, finer needle-shaped ettringite structure appears in the product, and more thin-flaked C-S-H gel is formed. A large amount of needle-shaped ettringite and thin-flaked gel fill the gaps between the particles, forming a denser structure inside the sample, which is reflected in the improvement of the compressive strength of the sample on a macro scale.

[0034] The present invention selects phosphogypsum, slag powder, cement and crushed stone as basic raw materials, designs different mix ratios, prepares road base materials according to the mix ratio scheme, and detects the mechanical indexes of the road base materials after stirring to form a mixture. The mechanical properties of the road base materials under different mix ratios are compared and analyzed to obtain the best mix ratio of slag powder and cement; the self-compacting properties and mechanical properties of the road base materials under different phosphogypsum dosages, slag powder and cement best mix ratios are compared and analyzed to determine the best mix ratio of each component.

[0035] The invention can quickly and accurately obtain the mix ratio of each component of the base material through indoor tests, and can be widely applied to base road filling, which is beneficial to solving the problems of large-scale stacking of phosphogypsum, occupation of land resources, environmental pollution, etc., saving a large amount of precious land resources, realizing the green recycling of industrial solid waste, reducing the cost of road engineering, improving engineering quality, and having good economic, environmental, and social benefits and broad application prospects.

[0036] In the following embodiments and comparative examples, phosphogypsum aged for two years from Yichang Xinyangfeng was used, and the agglomeration phenomenon of the original aged phosphogypsum was solved by crushing and fine granulation, with a particle size of less than 5 mm. The phosphogypsum raw materials were fully turned and dried to below the plastic limit, and were dispersed in powder form with a free moisture content of less than 12%.

[0037] Refer to the "Ordinary Concrete Mix Design Code" (JGJ55-2011), and the preparation strength is determined by referring to the following formula: f cu,0 ≥ f cu,k +1.645σ f cu,0 ---Preparation strength (MPa); f cu,k --- Design strength (MPa); σ---Strength standard deviation (MPa). According to the "Concrete Strength Test and Assessment Standard" GB / T50107-2010, the calculated laboratory test block strength standard deviation σ=3.13MPa.

[0038] The original road base design index is that the unconfined compressive strength of the upper and lower bases is not less than 4.0MPa, and the unconfined compressive strength of the subbase is not less than 3.0MPa. The prepared strength is about: the upper and lower bases are not less than 9.15MPa, and the subbase is not less than 8.15MPa.

[0039] Performance Test: The self-compacting properties of the self-compacting phosphogypsum base materials of the following examples and comparative examples were tested with reference to JGJ / T283-2012 "Technical Specifications for Application of Self-Compacting Concrete" and the test methods in Appendix A thereof and "Specifications for Mix Design of Ordinary Concrete" (JGJ55-2011).

[0040] Embodiment 1: This embodiment provides a self-compacting phosphogypsum base material, the base material comprising phosphogypsum, a cementitious material, an aggregate, an admixture and water, wherein the cementitious material is S95-grade granulated blast furnace slag powder and 42.5-grade ordinary Portland cement, and the aggregate is a mixture of sand and crushed stone; the base material is made by mixing the following components in mass percentage: phosphogypsum 40%, crushed stone 41.5%, machine-made sand 10%, cement 2%, slag powder 6.0%, and admixture 0.5%; The preparation method of phosphogypsum comprises crushing phosphogypsum aged for two years into fine particles to obtain phosphogypsum particles with a size of less than 5 mm, and fully drying the phosphogypsum until the particles are below the plastic limit and dispersed in powder form, and the free moisture content should be less than 12%; then, the phosphogypsum is placed in a ball mill for ball milling to obtain a particle size of 5-50 μm. The sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone adopts continuous graded crushed stone, with a particle size of 5-10mm, accounting for 30%; the particle size is 10-20mm, accounting for 70%; The sand-to-gravel ratio is 0.241; the water-to-cement ratio is 6.8; The admixtures are ester polycarboxylic acid water reducer, citric acid and polypropylene fiber, with a mass ratio of 1:0.3:0.02.

[0041] This embodiment also provides a method for preparing a self-compacting phosphogypsum base material, comprising the following steps: S1. Weigh each raw material according to mass percentage and set aside; S2. To the mixer, 85% of the total amount of phosphogypsum and 65% of the total amount of water were added and stirred at a stirring speed of 150 r / min for 2 min to form a first mixture; S3. Add the cementitious material, the remaining phosphogypsum, aggregate, admixture and the remaining water to the mixer and stir at a stirring speed of 150 r / min for 3 min to form a second mixture; S4. Add the first mixture to the second mixture of S3 and stir at 150r / min for 3min to form a third mixture; S5. Fill the formed third mixture into a molding mold, and after static molding, a self-compacting phosphogypsum road base material is formed.

[0042] Embodiment 2: This embodiment provides a self-compacting phosphogypsum base material, the base material comprising phosphogypsum, a cementitious material, an aggregate, an admixture and water, wherein the cementitious material is S95-grade granulated blast furnace slag powder and 42.5-grade ordinary Portland cement, and the aggregate is a mixture of sand and crushed stone; the base material is made by mixing the following components in mass percentage: phosphogypsum 45%, crushed stone 38.5%, machine-made sand 9%, cement 2%, slag powder 5.0%, and admixture 0.5%; The preparation method of phosphogypsum comprises crushing phosphogypsum aged for two years into fine particles to obtain phosphogypsum particles with a size of less than 5 mm, and fully drying the phosphogypsum to below the plastic limit, dispersing the phosphogypsum in powder form, and the free moisture content should be less than 12%; then placing the phosphogypsum in a ball mill for ball milling to obtain a phosphogypsum particle size of 5-50 μm; The sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone adopts continuous graded crushed stone, with a particle size of 5-10mm, accounting for 30%; the particle size is 10-20mm, accounting for 70%; The sand-to-gravel ratio is 0.234; the water-to-cement ratio is 6.125; The admixtures are ester polycarboxylic acid water reducer, citric acid and polypropylene fiber, with a mass ratio of 1:0.3:0.02.

[0043] The preparation method is the same as Example 1.

[0044] Embodiment 3: This embodiment provides a self-compacting phosphogypsum base material, the base material comprising phosphogypsum, a cementitious material, an aggregate, an admixture and water, wherein the cementitious material is S95-grade granulated blast furnace slag powder and 42.5-grade ordinary Portland cement, and the aggregate is a mixture of sand and crushed stone; the base material is made by mixing the following components in mass percentage: 55% phosphogypsum, 30.5% crushed stone, 7% machine-made sand, 2% cement, 5.0% slag powder, and 0.5% admixture; The preparation method of phosphogypsum comprises crushing phosphogypsum aged for two years into fine particles to obtain phosphogypsum particles with a size of less than 5 mm, and fully drying the phosphogypsum to below the plastic limit, dispersing the phosphogypsum in powder form, and the free moisture content should be less than 12%; then placing the phosphogypsum in a ball mill for ball milling to obtain a phosphogypsum particle size of 5-50 μm; The sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone adopts continuous graded crushed stone, with a particle size of 5-10mm, accounting for 30%; the particle size is 10-20mm, accounting for 70%; The sand-to-gravel ratio is 0.230; the water-to-cement ratio is 7; The admixtures are ester polycarboxylic acid water reducer, citric acid and polypropylene fiber, with a mass ratio of 1:0.3:0.02.

[0045] The preparation method is the same as Example 1.

[0046] Embodiment 4: This embodiment provides a self-compacting phosphogypsum base material, the base material comprising phosphogypsum, a cementitious material, an aggregate, an admixture and water, wherein the cementitious material is S95-grade granulated blast furnace slag powder and 42.5-grade ordinary Portland cement, and the aggregate is a mixture of sand and crushed stone; the base material is made by mixing the following components in mass percentage: phosphogypsum 45%, crushed stone 40.6%, machine-made sand 10%, cement 2%, slag powder 2.0%, and admixture 0.4%; The preparation method of phosphogypsum comprises crushing phosphogypsum aged for two years into fine particles to obtain phosphogypsum particles with a size of less than 5 mm, and fully drying the phosphogypsum to below the plastic limit, dispersing the phosphogypsum in powder form, and the free moisture content should be less than 12%; then placing the phosphogypsum in a ball mill for ball milling to obtain a phosphogypsum particle size of 5-50 μm; The sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone adopts continuous graded crushed stone, with a particle size of 5-10mm, accounting for 30%; the particle size is 10-20mm, accounting for 70%; The sand-to-gravel ratio is 0.256; the water-to-cement ratio is 4.4; The admixtures are ester polycarboxylic acid water reducer, citric acid and polypropylene fiber, with a mass ratio of 1:0.3:0.02.

[0047] The preparation method is the same as that of Example 1.

[0048] Embodiment 5: This embodiment provides a self-compacting phosphogypsum base material, the base material comprising phosphogypsum, a cementitious material, an aggregate, an admixture and water, wherein the cementitious material is S95-grade granulated blast furnace slag powder and 42.5-grade ordinary Portland cement, and the aggregate is a mixture of sand and crushed stone; the base material is made by mixing the following components in mass percentage: phosphogypsum 45%, crushed stone 37.5%, machine-made sand 9%, cement 2%, slag powder 6.0%, and admixture 0.5%; The preparation method of phosphogypsum comprises crushing phosphogypsum aged for two years into fine particles to obtain phosphogypsum particles with a size of less than 5 mm, and fully drying the phosphogypsum until the particles are below the plastic limit and dispersed in powder form, and the free moisture content should be less than 12%; then, the phosphogypsum is placed in a ball mill for ball milling to obtain a particle size of 5-50 μm. The sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone adopts continuous graded crushed stone, with a particle size of 5-10mm, accounting for 30%; the particle size is 10-20mm, accounting for 70%; The sand-to-gravel ratio is 0.240; the water-to-cement ratio is 6.8; The admixtures are ester polycarboxylic acid water reducer, citric acid and polypropylene fiber, with a mass ratio of 1:0.3:0.02.

[0049] The preparation method is the same as that of Example 1.

[0050] Embodiment 6: This embodiment provides a self-compacting phosphogypsum base material, the base material comprising phosphogypsum, a cementitious material, an aggregate, an admixture and water, wherein the cementitious material is S95 grade granulated blast furnace slag powder and 42.5 grade ordinary Portland cement, and the aggregate is a mixture of sand and crushed stone; the base material is made by mixing the following components in mass percentage: phosphogypsum 45%, crushed stone 35.1%, machine-made sand 8.2%, cement 2%, slag powder 9.0%, and admixture 0.7%; The moisture content of the phosphogypsum is less than 12%, and the particle size of the phosphogypsum is 5-50 μm; The sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone adopts continuous graded crushed stone, with a particle size of 5-10mm, accounting for 30%; the particle size is 10-20mm, accounting for 70%; The sand-to-gravel ratio is 0.234; the water-to-cement ratio is 9; The admixtures are ester polycarboxylic acid water reducer, citric acid and polypropylene fiber, with a mass ratio of 1:0.3:0.02.

[0051] The preparation method is the same as Example 1.

[0052] Embodiment 7: This embodiment provides a self-compacting phosphogypsum base material, the base material comprising phosphogypsum, a cementitious material, an aggregate, an admixture and water, wherein the cementitious material is S95-grade granulated blast furnace slag powder and 42.5-grade ordinary Portland cement, and the aggregate is a mixture of sand and crushed stone; the base material is made by mixing the following components in percentage by mass: phosphogypsum 45%, crushed stone 37.7%, machine-made sand 9%, cement 2%, slag powder 6.0%, and admixture 0.3%; The preparation method of phosphogypsum comprises crushing phosphogypsum aged for two years into fine particles to obtain phosphogypsum particles with a size of less than 5 mm, and fully drying the phosphogypsum to below the plastic limit, dispersing the phosphogypsum in powder form, and the free moisture content should be less than 12%; then placing the phosphogypsum in a ball mill for ball milling to obtain a phosphogypsum particle size of 5-50 μm; The sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone adopts continuous graded crushed stone, with a particle size of 5-10mm, accounting for 30%; the particle size is 10-20mm, accounting for 70%; The sand-to-gravel ratio is 0.239; the water-to-cement ratio is 7.4; The admixtures are ester polycarboxylic acid water reducer, citric acid and polypropylene fiber, with a mass ratio of 1:0.3:0.02.

[0053] The preparation method is the same as Example 1.

[0054] Embodiment 8: This embodiment provides a self-compacting phosphogypsum base material, the base material comprising phosphogypsum, a cementitious material, an aggregate, an admixture and water, wherein the cementitious material is S95-grade granulated blast furnace slag powder and 42.5-grade ordinary Portland cement, and the aggregate is a mixture of sand and crushed stone; the base material is made by mixing the following components in mass percentage: phosphogypsum 45%, crushed stone 37.5%, machine-made sand 9.0%, cement 2.2%, slag powder 5.9%, and admixture 0.4%; The preparation method of phosphogypsum comprises crushing phosphogypsum aged for two years into fine particles to obtain phosphogypsum particles with a size of less than 5 mm, and fully drying the phosphogypsum to below the plastic limit, dispersing the phosphogypsum in powder form, and the free moisture content should be less than 12%; then placing the phosphogypsum in a ball mill for ball milling to obtain a phosphogypsum particle size of 5-50 μm; The sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone adopts continuous graded crushed stone, with a particle size of 5-10mm, accounting for 30%; the particle size is 10-20mm, accounting for 70%; The sand-to-gravel ratio is 0.240; the water-to-cement ratio is 6.7; The admixtures are ester polycarboxylic acid water reducer, citric acid and polypropylene fiber, with a mass ratio of 1:0.3:0.02.

[0055] The preparation method is the same as Example 1.

[0056] Embodiment 9: This embodiment provides a self-compacting phosphogypsum base material, the base material comprising phosphogypsum, a cementitious material, an aggregate and an admixture, wherein the cementitious material is S95-grade granulated blast furnace slag powder and 42.5-grade ordinary Portland cement, and the aggregate is a mixture of sand and crushed stone; the base material is made by mixing the following components in mass percentage: phosphogypsum 45%, crushed stone 37.5%, machine-made sand 9.2%, cement 2.14%, slag powder 5.84%, and admixture 0.31%; The preparation method of phosphogypsum comprises crushing phosphogypsum aged for two years into fine particles to obtain phosphogypsum particles with a size of less than 5 mm, and fully drying the phosphogypsum to below the plastic limit, dispersing the phosphogypsum in powder form, and the free moisture content should be less than 12%; then placing the phosphogypsum in a ball mill for ball milling to obtain a phosphogypsum particle size of 5-50 μm; The sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone adopts continuous graded crushed stone, with a particle size of 5-10mm, accounting for 30%; the particle size is 10-20mm, accounting for 70%; The admixtures are ester polycarboxylic acid water reducer, citric acid and polypropylene fiber, with a mass ratio of 1:0.3:0.02.

[0057] The sand-to-gravel ratio is 0.245; the water-to-cement ratio is 6.97; The preparation method is the same as Example 1.

[0058] Comparative Example 1: The comparative example provides a self-compacting phosphogypsum base material, the base material comprising phosphogypsum, a cementitious material, an aggregate, an admixture and water, wherein the cementitious material is S95-grade granulated blast furnace slag powder and 42.5-grade ordinary Portland cement, and the aggregate is a mixture of sand and crushed stone; the base material is prepared by mixing the following components in mass percentage: 60% phosphogypsum, 25.5% crushed stone, 6% machine-made sand, 2% cement, 6.0% slag powder and 0.5% admixture; The preparation method is the same as Example 1.

[0059] Comparative Example 2: The present comparative example provides a self-compacting phosphogypsum base material, the base material comprising phosphogypsum, a cementitious material, an aggregate, an admixture and water, wherein the cementitious material is S95 grade granulated blast furnace slag powder and 42.5 grade ordinary Portland cement, and the aggregate is a mixture of sand and crushed stone; the base material is prepared by mixing the following components by mass percentage: phosphogypsum 85%, cement 2%, slag powder 12.0%, and admixture 1.0%; The preparation method is the same as that of Example 1.

[0060] Comparative Example 3: The comparative example provides a self-compacting phosphogypsum base material, the base material comprising phosphogypsum, a cementitious material, an aggregate, an admixture and water, wherein the cementitious material is S95-grade granulated blast furnace slag powder and 42.5-grade ordinary Portland cement, and the aggregate is a mixture of sand and crushed stone; the base material is prepared by mixing the following components in mass percentage: phosphogypsum 45%, crushed stone 32.3%, machine-made sand 7.6%, cement 2%, slag powder 12.0%, and admixture 1.1%; The preparation method is the same as Example 4.

[0061] Comparative Example 4: The comparative example provides a self-compacting phosphogypsum base material, the base material comprising phosphogypsum, a cementitious material, an aggregate, an admixture and water, wherein the cementitious material is S95-grade granulated blast furnace slag powder and 42.5-grade ordinary Portland cement, and the aggregate is a mixture of sand and crushed stone; the base material is prepared by mixing the following components by mass percentage: phosphogypsum 45%, crushed stone 29.6%, machine-made sand 6.9%, cement 2%, slag powder 15.0%, and admixture 1.5%; The preparation method is the same as Example 4.

[0062] Comparative Example 5: The comparative example provides a self-compacting phosphogypsum base material, the base material comprising phosphogypsum, a cementitious material, an aggregate, an admixture and water, wherein the cementitious material is S95-grade granulated blast furnace slag powder and 42.5-grade ordinary Portland cement, and the aggregate is a mixture of sand and crushed stone; the base material is prepared by mixing the following components by mass percentage: phosphogypsum 45%, crushed stone 41.8%, machine-made sand 6.0%, cement 2%, slag powder 5.0%, and admixture 0.2%; The preparation method is the same as Example 4.

[0063] The self-compacting properties and mechanical properties of the phosphogypsum road base material samples of the above Examples 1-9 and Comparative Examples 1-5 were tested, and the results are shown in Table 1.

[0064] Table 1 Test results of self-compacting properties and mechanical properties of different phosphogypsum road base materials

[0065] From the data analysis in Table 1, it can be seen from the comparison between Examples 1-3 and Comparative Examples 1-2 that the 85% high-dosage phosphogypsum self-compacting base material has poor cohesion, fast collapse and expansion speed, long final setting time, shrinkage and cracking on the surface of the test block after molding, and low strength; the 60% phosphogypsum self-compacting base material has a long final setting time and low strength; the 45% and 40% phosphogypsum crushed stone self-compacting base materials have good cohesion, workability, and fluidity, and the strength meets the requirements. That is, with the increase of the phosphogypsum dosage, the compressive strength of the phosphogypsum self-compacting base material shows a downward trend, indicating that excessive phosphogypsum dosage is not conducive to the enhancement of compressive strength.

[0066] In order to avoid the occurrence of early pests and diseases, and cement mainly plays a role in stimulating the hydration activity of slag powder, the present invention selects a relatively small cement dosage to investigate the slag powder dosage. By comparing Examples 4-9 and Comparative Examples 3-4, it can be seen that when the cement dosage is constant, as the slag powder dosage increases, the 28-day strength gradually increases; but if the slag powder is excessive and its mass ratio to cement is higher than 4.5, the 28-day strength growth is not obvious; in addition, if the slag powder dosage is too high, the shrinkage is large, the early strength is low, the activity of the excessive slag powder is not stimulated early, and the later strength continues to rise, which is easy to cause local cracks.

[0067] In Examples 1-4, the 28-day unconfined compressive strength is low, and the strength difference between 14 days and 28 days is large, indicating that the cementitious material is not completely hydrated, which is not conducive to the stability of the base material. In Comparative Examples 1-5, the self-compactness and compressive strength of the materials cannot meet the preparation requirements. In Examples 5-9, the 28-day unconfined compressive strength is greater than 9.45Mpa, meeting the strength requirements of the "Concrete Strength Test and Evaluation Standard", and there is no obvious difference in the strength between 14 days and 28 days in Example 9, indicating that calcium aluminate is not continuously generated with the increase of age, and the base structure is relatively stable as a whole.

[0068] In summary, the phosphogypsum road base material of the present invention, under the ratio of 45% phosphogypsum + 2.14% cement + 5.84% mineral powder and a water-cement ratio of 6.97, meets the preparation strength requirements, has low cost, and has stable strength for 14-28 days; and can be widely used in base road construction.

[0069] Test example This experiment provides a self-compacting phosphogypsum road base, which is paved using the phosphogypsum base material of Example 9.

[0070] The test section is the motor vehicle lane of the Dianjun 1st Road (Juanqiaohe 2nd Road-Wulong 3rd Road) municipal engineering EPC project, i.e. K1+310~K1+490, a total of 170 meters. The phosphogypsum road base is used for engineering verification tests, and the following test methods are used to conduct performance testing and economic and social benefit evaluation on the road base of the engineering test.

[0071] With reference to JGJ / T283-2012 "Technical Code for Application of Self-compacting Concrete" and its Appendix A.1, the self-compacting performance of the engineering verification test core samples was tested.

[0072] Referring to GBT / 50784-2013 "Technical Standard for On-site Testing of Concrete Structures", the mechanical properties of on-site core samples and standard-cured test blocks were tested.

[0073] According to the water absorption grade and test method of JGT / 266 "Foamed Concrete", the water absorption of on-site core samples and standard curing test blocks was tested.

[0074] With reference to the “Horizontal Oscillation Method for Leaching Toxicity of Solid Waste”, pollutants in self-compacting phosphogypsum road base materials were tested.

[0075] 1. Performance testing 1.1 Filling test The filling performance needs to test two indicators: slump expansion and expansion time. The test results are shown in Table 2.

[0076] Table 2 Slump expansion and expansion time of base material mixture

[0077] It can be seen from Table 2 that the slump expansion grade of the self-compacting phosphogypsum base material of the road base is SF1, and the expansion time (T 500 ) level is VS1, meeting the technical index requirements.

[0078] 1.2 Compressive strength The compressive strength after 7 days, 14 days and 28 days was measured by coring in the field test section and standard curing test blocks in the laboratory. The test results are shown in Table 3.

[0079] Table 3 Compressive strength test of on-site core samples and standard curing test blocks

[0080] It can be seen from Table 3 that through the coring of the on-site test section and the standard curing test blocks in the laboratory, the 28-day compressive strength can reach more than 5MPa, meeting the technical index requirements.

[0081] 1.3 Softening coefficient The 14-day-old field core samples and standard-cured test blocks were divided into two groups. One group was immersed in water for 14 to 28 days, and its strength was tested. The strength was compared with that of the core samples and standard-cured test blocks at normal 28 days of age to obtain the 28-day water softening coefficient. The results are shown in Table 4.

[0082] Table 4 Water softening resistance test of on-site core samples and standard curing test blocks

[0083] It can be seen from Table 4 that after testing, the water softening coefficient is far more than 85%, and the core sample water-soaked strength is better than the strength growth under natural conditions, meeting the technical index requirements.

[0084] 1.4 Water absorption The water absorption rate of the 28-day-old field core samples and standard-cured test blocks was tested, and the data is shown in Table 7.

[0085] Table 5 Water absorption test of on-site core samples and standard curing test blocks

[0086] As shown in Table 5, the water absorption of the 28-day-old field core samples and standard-cured test blocks was tested, and the average water absorption was 5.57% and 5.58% respectively, both meeting the technical index requirements.

[0087] 1.5 XRD X-ray diffraction analysis was performed on samples of the self-compacting phosphogypsum base material mixture at 14d and 28d. The analysis results are shown in Figure 1 .

[0088] Comparing the XRD patterns of 14d and 28d samples of self-compacting phosphogypsum base materials, it can be seen that the content of ettringite is low and there is no obvious difference between the two ages, indicating that ettringite is not continuously generated with the increase of age, which is beneficial to the overall stability of the base structure.

[0089] 1.6 Environmental Assessment The adverse impact that self-compacting phosphogypsum base materials may have on the environment is mainly the precipitation of pollutants into the soil and surrounding environment after long-term immersion or scouring by rainwater. Therefore, the solid waste leaching toxicity leaching method is used to test it, and the test method adopts the horizontal oscillation method. The pollutant indicators of the core sample leachate of the self-compacting phosphogypsum base material at the age of 28 days are tested, and the results are shown in Table 6.

[0090] Table 6 Test results of pollutant precipitation in the leaching solution of core samples at 28 days of age

[0091] After the test section was implemented, the leachate of the core sample of the self-compacting phosphogypsum base material in the test section at a age of 28 days was tested. The test results showed that after solidification and modification, the content of harmful substances in the leachate of the material was very low, which met the requirements of the emission standards and satisfied the environmental protection goals of the test section.

[0092] Based on the above test results, it can be seen that the self-compacting performance, mechanical properties and environmental impact of the road base paved with self-compacting phosphogypsum base material meet the technical standards.

[0093] 2. Economic and social benefits 2.1 Economic Benefits The economic comparison between self-compacting phosphogypsum base material and 5% cement stabilized crushed stone is shown in Table 7.

[0094] Table 7 Comparison of economic performance between self-compacting phosphogypsum base material and 5% cement stabilized crushed stone

[0095] It can be seen from the data in Table 7 that the overall cost of self-compacting phosphogypsum base material (45% phosphogypsum) used for road base is basically the same as that of conventional 5% cement-stabilized crushed stone base. If the large-scale comprehensive application of phosphogypsum in engineering in the later stage is taken into account, the cost of phosphogypsum raw materials and production costs will have a large downward space, and the promotion and application prospects are broad, with significant economic benefits.

[0096] 2.2 Social Benefits As solid waste, phosphogypsum replaces a large amount of aggregates in the road base. According to the stable base of 35,000 tons per highway of urban trunk roads, 45% phosphogypsum, about 15,800 tons of phosphogypsum slag is consumed per kilometer, which is equivalent to saving 15,800 tons of natural aggregates. It can better realize the resource utilization and large-scale efficient utilization of industrial waste slag, and produce good social benefits. At the same time, it greatly alleviates the difficulties of road engineering construction in areas with scarce mining stone resources, which is conducive to saving resources, energy saving and consumption reduction, and sustainable development of urban construction.

[0097] In summary, the present invention provides a self-compacting phosphogypsum base material and a preparation method thereof, which base material not only plays a role in quickly consuming phosphogypsum and reducing inventory stacking pressure, thereby achieving the effect of resource utilization and turning waste into treasure, but also has good fluidity and high mechanical strength; when used for base road construction, its filling performance, compressive strength, water absorption, softening coefficient, unstable substance crystal phase analysis and pollutant index can all meet the road base performance requirements, construction work performance requirements and pollutant emission and other related requirements, with significant economic and social benefits, and can be widely used in road bases of municipal and highway projects.

[0098] The above embodiments are only preferred technical solutions of the present invention and should not be regarded as limiting the present invention. The protection scope of the present invention shall be the technical solutions recorded in the claims, including equivalent replacement solutions of the technical features in the technical solutions recorded in the claims. That is, equivalent replacement improvements within this scope are also within the protection scope of the present invention.

Claims

1. A self-compacting phosphogypsum road base material, characterized in that: The base material includes phosphogypsum, cementitious material, aggregate, admixture and water, and each solid component is calculated in the following mass percentages: phosphogypsum 40-55%, cementitious material 4-13%, aggregate 35-50%, admixture 0.2-0.7%, and water-cement ratio 4.5-7.

5.

2. The self-compacting phosphogypsum road base material according to claim 1, characterized in that: The moisture content of the phosphogypsum is lower than 12%, and the particle size of the phosphogypsum is 5-45 μm.

3. The self-compacting phosphogypsum road base material according to claim 1, characterized in that: The cementitious materials are S95 grade granulated blast furnace slag powder and 42.5 grade ordinary Portland cement; The mass ratio of the 42.5 grade ordinary Portland cement is 1-4%, and the mass ratio of the S95 grade slag powder is 3-9%.

4. The self-compacting phosphogypsum road base material according to claim 1, characterized in that: The aggregate is a mixture of sand and crushed stone, and the sand is machine-made fine sand with a particle size of less than 4.75 mm; The crushed stone is graded crushed stone, which is fine crushed stone with a particle size of 5-10 mm and coarse crushed stone with a particle size of 10-20 mm, and the mass ratio is 3:

7.

5. The self-compacting phosphogypsum road base material according to claim 3, characterized in that: The mass ratio of the cement to the slag powder is 1:1.5-4.

5.

6. The self-compacting phosphogypsum road base material according to claim 1, characterized in that: The admixtures include slow-release agents and water reducers, accounting for 0.3-0.4% of the total mass of the mixture.

7. The self-compacting phosphogypsum road base material according to claim 6, characterized in that: The water reducer is a polycarboxylic acid water reducer, and the retarder is citric acid, and the mass ratio is 1:0.1-0.

3.

8. The self-compacting phosphogypsum road base material according to claim 1, characterized in that: The base material includes phosphogypsum, cementitious material, aggregate, admixture and water, and the components are calculated in the following mass percentages: phosphogypsum 40-50%, cementitious material 6-10%, aggregate 40-50%, admixture 0.3-0.4%, and water-cement ratio 6.5-7.

5.

9. The method for preparing the self-compacting phosphogypsum road base material according to claim 1, comprising the following steps: S1. Weigh each raw material according to mass percentage and set aside; S2. Take part of the phosphogypsum and an appropriate amount of water and mix them in a mixer, mix them evenly to form a first mixture; S3. The cementitious material, the remaining phosphogypsum, aggregate, admixture and the remaining water are mixed in a mixer and mixed to form a second mixture; S4. Add the first mixture to the second mixture and mix and stir to form a third mixture; S5. Fill the formed third mixture into a molding mold, and after standing and molding, a self-compacting phosphogypsum road base material is formed. Among them, in S2, the amount of phosphogypsum is 80-90% of the total amount, and the amount of water is 60-70% of the total amount.

10. The method for preparing a self-compacting phosphogypsum road base material according to claim 8, characterized in that: In S2, the stirring speed of phosphogypsum and water is 100-200 r / min, and the time is 1-3 min; In S3, the stirring speed of each component is 100-200r / min, and the time is 2-4min; In S4, the stirring speed of each component is 100-200r / min, and the time is 3-6min.

Citation Information

Patent Citations

  • Self-compacting concrete prepared from industrial solid wastes and preparation method thereof

    CN104761229A

  • Phosphogypsum cement graded broken stone stable layer and preparation method thereof

    CN108516781A

  • Phosphogypsum supersulfide slag cement stable layer, phosphogypsum-based cementing material thereof and preparation method of phosphogypsum supersulfide slag cement stable layer

    CN111848080A

  • Modified ardealite stabilized macadam as well as preparation method and application thereof

    CN113754398A

  • Production of self-packing concrete

    JP1994219809A

Cited By

  • High-content phosphogypsum pavement base material and preparation method thereof

    CN120794554A

  • High-content phosphogypsum pavement base material and preparation method thereof

    CN120794554B

  • Phosphogypsum-based fine aggregate as well as preparation method and application thereof

    CN121850420A